The Use of Supplementary Materials for Teaching Children in EFL Classes - Tomalá Guamanquishpe, Maria Fernanda (2013)
The present work concerns about the use of supplementary materials for teaching children in EFL classes, with the purpose of determining and analyzing the type of supporting materials employed. The research was conducted in Madrid, in the Nazareth Oporto School. The research sample consisted of two teachers and eighty-seven students of the third, fourth and fifth grades of elementary school. Besides, the data was collected through direct observation, the interview and a literature review. Also, the qualitative and quantitative approach were applied for the development of this study. Thus, the qualitative analysis was related to the pertinence, appropriateness and quality of the applied supplementary materials. It revealed that most of these resources influenced positively in the achievement of the goals. And, its use was appropriate to the student´s age and level of understanding. Additionally, the quantitative analysis reflected that the visual and audio resources were the most used supplementary materials. Just the opposite happened with websites, movies and videos. But teachers and students considered that the use of this materials improves both the linguistic competence and students motivation.